Gentes e divindades na Lusitânia pré-romana ocidental (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2019)
Four exemplars of roman epigraphic monuments are presented. Two of them can instigate us to be more prudent in considering indigenous names that by the first time are documented in Hispania, because they can be Latin, as the recent and larger investigation learns us.Third example: a tessera that possibly we classify as a tessera paganica, with the questions that this kind of documentation carries to us.Two monuments of Alcains (civitas Igaeditanorum) can demonstrate that indigenous gentilitates had their name of their first ancestor and, therefore, we can better understand http://eda-bea.es/, nº 22 943.